Cytotoxicity of Medicinal Plant Species Used by Traditional Healers in Treating People Suffering From HIV/AIDS in Uganda - Anywar, Godwin Upoki; Kakudidi, Esezah; Oryem-Origa, Hannington; Schubert, Andreas; Jassoy, Christian (Frontiers in Toxicology, 2022)
Introduction: Many people living with HIV/AIDS (PLHIV) in Uganda widely use herbal medicines. However, their toxicity and safety have not been investigated. The use of these plants can potentially cause harmful effects to the health of patients. The purpose of this study was to determine the cytotoxicity of some commonly used medicinal plant species used by PLHIV. Methods: The cytotoxicity of the plant extracts was determined with the AlamarBlue cell viability assay using the human glioblastoma cell line U87.CD4.CXCR4. The cells were treated with varying concentrations of extracts of Warburgia ugandensis, Erythrina abyssinica, Cryptolepis sanguinolenta, Albizia coriaria, Psorospermum febrifugium, Gymnosporia senegalensis, Zanthoxylum chalybeum, Securidaca longipendunculata, Vachellia hockii, Gardenia ternifolia, and Bridelia micrantha reconstituted with ethanol and dimethyl sulfoxide (DMSO). Using regression analysis, the half maximal cytotoxic concentration (CC50) of the plant extracts were calculated from exponential curve fits, since they provided the highest coefficient of determination, R2. Results: The ethanol extracts of W. ugandensis (CC50 = 7.6 μg/ml) and A. coriaria (CC50 = 1.5 μg/ml) as well as the DMSO-reconstituted extracts of W. ugandensis (CC50 = 6.4 μg/ml) and A. coriria (CC50 = < 4 μg/ml) were highly cytotoxic. The cytotoxicity of W. ugandensis and A. coriaria compared well with the indigenous traditional knowledge of the toxic effects experienced when the plants were not used correctly. However, the cytotoxicity of most of the plant extracts (15/22) was low to moderate (CC50 = 21–200 μg/ml). Conclusion: Most of the plant species tested in this study had low to moderate cytotoxicity against U87.CD4.CXCR4 cells, except W. ugandensis and A. coriria which were highly cytotoxic.